RNAi suppression of DNA methylation affects the drought stress response and genome integrity in transgenic poplar. Issue 1 (16th July 2021) - Sow, Mamadou D.; Le Gac, Anne‐Laure; Fichot, Régis; Lanciano, Sophie; Delaunay, Alain; Le Jan, Isabelle; Lesage‐Descauses, Marie‐Claude; Citerne, Sylvie; Caius, Jose; Brunaud, Véronique; Soubigou‐Taconnat, Ludivine; Cochard, Hervé; et al.
Summary: Trees are long‐lived organisms that continuously adapt to their environments, a process in which epigenetic mechanisms are likely to play a key role. Via downregulation of the chromatin remodeler DECREASED IN DNA METHYLATION 1 (DDM1) in poplar ( Populus tremula  ×  Populus alba ) RNAi lines, we examined how DNA methylation coordinates genomic and physiological responses to moderate water deficit. We compared the growth and drought response of two RNAi‐ ddm1 lines to wild‐type (WT) trees under well‐watered and water deficit/rewatering conditions, and analyzed their methylomes, transcriptomes, mobilomes and phytohormone contents in the shoot apical meristem. The RNAi‐ ddm1 lines were more tolerant to drought‐induced cavitation but did not differ in height or stem diameter growth. About 5000 differentially methylated regions were consistently detected in both RNAi‐ ddm1 lines, colocalizing with 910 genes and 89 active transposable elements. Under water deficit conditions, 136 differentially expressed genes were found, including many involved in phytohormone pathways; changes in phytohormone concentrations were also detected. Finally, the combination of hypomethylation and drought led to the mobility of two transposable elements. Our findings suggest major roles for DNA methylation in regulation of genes involved in hormone‐related stress responses, and the maintenance of genome integrity through repression of transposable elements.